Characterisation of endogenous A2A and A2B receptor-mediated cyclic AMP responses in HEK 293 cells using the GloSensor™ biosensor: evidence for an allosteric mechanism of action for the A2B-selective antagonist PSB 603 - Goulding, Joelle; May, Lauren T.; Hill, Stephen J. (Elsevier, 2018)
Endogenous adenosine A2B receptors (A2BAR) mediate cAMP accumulation in HEK 293 cells. Here we have used a biosensor to investigate the mechanism of action of the A2BAR antagonist PSB 603 in HEK 293 cells. The A2A agonist CGS 21680 elicited a small response in these cells (circa 20% of that obtained with NECA), suggesting that they also contain a small population of A2A receptors. The responses to NECA and adenosine were antagonised by PSB 603, but not by the selective A2AAR antagonist SCH 58261. In contrast, CGS 21680 responses were not antagonised by high concentrations of PSB 603, but were sensitive to inhibition by SCH 58261. Analysis of the effect of increasing concentrations of PSB 603 on the response to NECA indicated a non-competitive mode of action yielding a marked reduction in the NECA EMAX with no significant effect on EC50 values. Kinetics analysis of the effect of PSB 603 on the A2BAR-mediated NECA responses confirmed a saturable effect that was consistent with an allosteric mode of antagonism. The possibility that PSB 603 acts as a negative allosteric modulator of A2BAR suggests new approaches to the development of therapeutic agents to treat conditions where adenosine levels are high.